Strategi Local-Sosiosaintific Issues Dengan OE3C Instructional Terhadap Kemampuan Literasi Sains Siswa Di Sekolah Dasar - Tasya Maulidiawati; Apri Irianto; Reza Rachmadtullah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Multiple pedagogical research have shown that guided inquiry-based learning increases students' scientific literacy. The Program for International Student Assessment (PISA) conducted a study of scientific literacy between 2000 and 2015, and their findings show that students in Indonesia still have a low level of scientific literacy compared to other OECD (Organization for Economic Co-operation and Development) countries. flat. Organization for Economic Co-operation and Development) countries. Thus, we set out to investigate whether or whether introducing the Local Socioscientific Issues (SSI) approach from the OE3C Instructional affected students' scientific literacy. A non-blinded pre-post experimental design was adopted for this study's quasi-quantitative method. Correlations between Local Socioscientific Issues (SSI) and OE3C Instructional methods and cyan enhancement. literacy were found in an analysis of obtained data using SPSS Version 26. Consequently, OE3C Instructional may be used to include the Local Socioscientific Issues (SSI) method into elementary school science instruction with the goal of improving students' scientific literacy.